Assessment of the Quality of the Saddang River as A Water Resource in North Toraja Regency Using Storet and Pollution Index - Reni Oktaviani Tarru; Juliah Sarira; Marianne Y Marrung; Harni Eirene Tarru; Yulius Pakiding (Politeknik Siber Cerdika Internasional, 2026)
Background: The Saddang River in North Toraja Regency serves as a key water resource for domestic, agricultural, and fishery needs. Increased activity along the watershed may degrade water quality and threaten the sustainability of the river's functions. Objective: This study aims to evaluate the water quality of the Saddang River as a water resource in North Toraja Regency using the STORET and Pollution Index methods. Methods: Sampling was conducted at four observation points (upstream, two middle stations, and downstream) over two weeks, measuring temperature, pH, DO, BOD, COD, TDS, and Total Coliform, with reference to class II water quality standards in Government Regulation Number 22 of 2021. Results: STORET classified the Saddang River as moderately polluted at all stations (scores: −11 to −15). The Pollution Index indicated more severe conditions: in Week 1, ST1 and ST4 were moderately polluted (IP 7.30–8.71) and ST2–ST3 were heavily polluted (IP 10.79–13.18); in Week 2, all stations were heavily polluted (IP 10.21–18.94). Dominant pollutants were Total Coliform, BOD, COD, and low DO (<4 mg/L), indicating organic and microbiological contamination from domestic sources. Water quality declined progressively from upstream to downstream. Conclusion: Both STORET and Pollution Index methods confirmed water quality degradation in the Saddang River, with Total Coliform, BOD, COD, and low DO as dominant pollutants. ST2 and ST3 were identified as critical pollution hotspots requiring priority intervention. The combined application of both methods provides a robust framework for evidence-based water resource management in North Toraja Regency.